INSPECTORATE SUPERVISION IN APPLYING COMPETITIVE PRINCIPLES IN MANAGING PROCUREMENT OF GOODS / SERVICES IN GOVERNMENT OF NORTH SULAWESI PROVINCE - Pakasi, Novrabella Clarashinta (ACCOUNTABILITY, 2018)
This paper examines the supervision of the Inspectorate on the application of the principle of competitiveness in the management of government goods/services procurement. This research was conducted at the North Sulawesi Provincial Government. The essence of this paper aims to find out whether the Inspectorate has supervised the application of the principle of competitiveness in the management of procurement of goods/services to the North Sulawesi Provincial Government. The methodology used in this study is qualitative. The techniques and procedures for collecting data through in-depth interviews with a number of informants related to the application of the principle of competitiveness in the management of procurement of goods/services. Activities in the analysis include data reduction, data display, and conclusion drawing/verification. The results of this study indicate that the Inspectorate has been maximal enough to carry out supervision of the application of the principle of competitiveness in the procurement of goods/services in North Sulawesi Province.Keywords : Inspectorate, Competing, Management, Goods/Services